LEARNERS’ PREFERENCES OF MULTIMEDIA RESOURCES IN AN EXTENSIVE LISTENING PROGRAM - Setyawan, Dimas; Ivone, Francisca Maria; Suryati, Nunung (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
Extensive listening has gained popularity in the past few years due to its benefits for foreign/second language learning. It improves language learners’ listening skills in a less stressful way because they can choose topics based on their interest or do the activity simply for enjoyment. Also, in the implementation, students may choose any multimedia resources in extensive listening activities. In this descriptive study, students’ preferences of multimedia resources used in extensive listening activities were explored. In addition, aspects of the resources they found easy and challenging and why they choose them were also investigated. Research data were collected from 109 learners’ extensive listening journals over a semester. Results of the data analysis indicated that there are 17 types of multimedia resources used by the students. Most of them selected the listening materials based on their interests and curiosity. Moreover, the speakers’ accent and speech rate, and limited vocabulary are aspects some students found challenging. Further studies may want to compare types of resources used and reasons for choosing them by high and low proficient listeners. How learners used the resources may also be of interest to future researchers.